Hydroponics and protected cultivation a practical guide - Morgan, Lynette, 1970- (CAB International, 2021)
"A comprehensive, practical text which covers a diverse range of hydroponic and protected cropping techniques, systems, greenhouse types and environments. It also covers related subjects such as the use of indoor plant factories, vertical systems, organic hydroponics, aquaponics and other systems"--